Features of the Vaginal and Vestibular Microbioma in Patients With Vestibulodynia: A Case-Control Study. Issue 3 (July 2020) - Murina, Filippo; Caimi, Camilla; Di Pierro, Francesco; Di Francesco, Stefania; Cetin, Irene
Abstract : Objective: Our objective was to determine the role of vaginal and/or vestibular microbiota disturbance as an associated factor of symptom characteristic of provoked vestibulodynia (PVD). Study Design: In an observational case-control study, the bacterial microbiomes in the vagina and vestibule from 20 women with PVD and 18 healthy controls were compared using a 16S rRNA gene-based molecular analysis. Clinical data were recorded through a 0- to 10-point visual analog scale related to dyspareunia and vulvovaginal pain/burning. Results: Comparative assessment of the bacterial taxa (cutoff ≥15%) revealed 105 genera in the vaginal samples of PVD patients and 113 genera in the vestibular samples. Similarly, 120 genera were detected in the vaginal samples and 151 in the vestibular samples of the control group. Bacterial complexity was higher in the vestibular samples than in vaginal samples in both groups, without statistically significant differences. The following 3 dominant taxonomic units were found: Lactobacillus, Gardnerella, and Atopobium in PVD patients and Lactobacillus, Gardnerella, and Bifidobacterium in the control group. Lactobacillus gasseri was dominant only in women with PVD, showing a significant correlation with burning/pain intensity and dyspareunia severity (0.255 and 0.357, respectively, p < .001). Conclusions: Our data suggest that bacterial communities in vaginal discharge are an important contributor to the vestibular microbiota. Lactobacillus gasseri may be an element of vulnerability toward the development of vaginal dysbiosis. We can postulate its association as a potential etiologic organism in some individuals, either by itself or in some combination with other trigger factors.